Penerapan Universal Design dalam Interior Panti Werdha di Bogor - Dwitiya Ken Saraswati; Stephanus Pantja Honggowidjaja; Anik Rakhmawati (Intra, 2019)
Elderly care is one solution to entrust parents, especially elderly people. However, the name of the nursing home itself is often viewed negatively by the community. Placing elderly people in nursing homes is deemed inappropriate because a child is considered unable to take care of his parents, even though they do it without reason. Along with the development of the times, a child's habit of caring for his parents is increasingly rare, due to a lot of busyness. In addition, it is not uncommon for the elderly to be entrusted to the place at their own discretion. For the elderly, they can be paid more attention to in nursing homes and can socialize with people of their age.This interior design aims to eradicate the stigma of the community towards the Elderly Care itself, which is able to provide optimal service to the elderly including physical, mental, and social development, as well as fulfilling all the needs of the elderly, especially those who get less attention from their own families. This elderly care is designed to provide comfort for the elderly by applying universal designs to their interiors, and also ergonomic furniture. Then it can be useful for many people, especially for the elderly in carrying out their daily activities and their life.